Spatial organization and mechanical properties of the pericellular matrix on chondrocytes - McLane, Louis T.; Chang, Patrick; Granqvist, Anna; Böhm, Heike; Kramer, Anthony; Scrimgeour, Jan; Curtis, Jennifer E. (Biophysical journal, 2013)
A voluminous polymer coat adorns the surface of many eukaryotic cells. Although the pericellular matrix (PCM) often extends several microns from the cell surface, its macromolecular structure remains elusive. This massive cellular organelle negotiates the cell’s interaction with surrounding tissue, influencing important processes such as cell adhesion, mitosis, locomotion, molecular sequestration, and mechanotransduction. Investigations of the PCM’s architecture and function have been hampered by the difficulty of visualizing this invisible hydrated structure without disrupting its integrity. In this work, we establish several assays to noninvasively measure the ultrastructure of the PCM. Optical force probe assays show that the PCM of rat chondrocyte joint (RCJ-P) cells easily reconfigures around optically manipulated microparticles, allowing the probes to penetrate into rather than compress the matrix. We report distinct changes in forces measured from PCMs treated with exogenous aggrecan, illustrating the assay’s potential to probe proteoglycan distribution. Measurements reveal an exponentially increasing osmotic force in the PCM arising from an inherent concentration gradient. With this result, we estimate the variation of the PCM’s mesh size (correlation length) to range from ∼100 nm at the surface to 500 nm at its periphery. Quantitative particle exclusion assays confirm this prediction and show that the PCM acts like a sieve. These assays provide a much-needed tool to study PCM ultrastructure and its poorly defined but important role in fundamental cellular processes.